(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
Shukur Kholmirzaev, as the owner of a unique personal artistic style, avoids criticism, one-sidedness, narrative. Although he is stingy with words, he only achieves full and bright delivery to the reader. However, sometimes his works give the impression that they are not finished. The reader waits for the continuation of the work. He does not draw portraits of heroes. seems to focus on character creation, makes the reader think, think deeply. The judgment passed on the heroes of the work is brought to the reader’s attention. This article discusses writer Shukur Kholmirzaev’s unique artistic style in his novel "Last Station".